Oxygen Limitation Enhances the Antimicrobial Activity of Fosfomycin in Pseudomonas aeruginosa Following Overexpression of glpT Which Encodes Glycerol-3-Phosphate/Fosfomycin Symporter - Hirakawa, Hidetada; Kurabayashi, Kumiko; Tanimoto, Koichi; Tomita, Haruyoshi (Frontiers in Microbiology, 2018)
Fosfomycin is resurfacing as a “last resort drug” to treat infections caused by multidrug resistant pathogens. This drug has a remarkable benefit in that its activity increases under oxygen-limited conditions unlike other commonly used antimicrobials such as β-lactams, fluoroquinolones and aminoglycosides. Especially, utility of fosfomycin has being evaluated with particular interest to treat chronic biofilm infections caused by Pseudomonas aeruginosa because it often encounters anaerobic situations. Here, we showed that P. aeruginosa PAO1, commonly used in many laboratories, becomes more susceptible to fosfomycin when grown anaerobically, and studied on how fosfomycin increases its activity under anaerobic conditions. Results of transport assay and gene expression study indicated that PAO1 cells grown anaerobically exhibit a higher expression of glpT encoding a glycerol-3-phosphate transporter which is responsible for fosfomycin uptake, then lead to increased intracellular accumulation of the drug. Elevated expression of glpT in anaerobic cultures depended on ANR, a transcriptional regulator that is activated under anaerobic conditions. Purified ANR protein bound to the DNA fragment from glpT region upstream, suggesting it is an activator of glpT gene expression. We found that increased susceptibility to fosfomycin was also observed in a clinical isolate which has a promoted biofilm phenotype and its glpT and anr genes are highly conserved with those of PAO1. We conclude that increased antibacterial activity of fosfomycin to P. aeruginosa under anaerobic conditions is attributed to elevated expression of GlpT following activation of ANR, then leads to increased uptake of the drug.